DDRE-34. TRIBBLES-1 (TRIB1) PSEUDOKINASE PROMOTES SURVIVAL OF GBM CELLS BY DECREASING RT/TMZ INDUCED APOPTOSIS. (9th November 2020) - Singh, Karnika; Han, Chunhua; Fleming, Jessica; McElroy, Joseph; Bell, Erica; Robe, Pierre; Haque, S Jaharul; Chakravarti, Arnab
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most aggressive form of glioma with a mean survival of 12 to 15 months after diagnosis. The current therapy involves administration of radiation therapy and temozolomide (TMZ). Due to poor survival outcome, new druggable therapeutic targets need to be identified for drug development. TRIB1 is a Ser/Thr pseudokinase that acts as a scaffold protein to mediate proteasomal degradation of its substrate proteins in the cell. TRIB1 has been associated with tumorigenesis and therapy resistance of several cancers, including HCC, NSCLC among others. In the present study we show that TRIB1 can promote GBM by increasing survival of GBM cells and reducing RT/TMZ-induced cell death. MATERIALS AND METHODS: We identified TRIB1 by statistical association (Cox regression analysis) of the patient-derived methylation data generated using 450K and EPIC methylation array. Functional validation of TRIB1 was done in vitro by overexpression and knockdown approaches. Doxycycline inducible system was used for TRIB1 knockdown. Stable cell lines were generated by puromycin selection. Western blotting was utilized to detect protein levels. RESULTS: The global methylation analysis on a Utrecht GBM cohort showed that TRIB1 promoter methylation was associated with better OS of GBM patients (HR = 0.81 (0.62–1.05); p = 0.11). We also observed that TRIB1 overexpression caused a decrease in apoptosis of patient-derived GBM cell lines after RT/TMZ treatment. Additionally, an increase in the phosphorylation of ERK and Akt was also noted. However, TRIB1 knockdown only led to decreased Akt phosphorylation. CONCLUSION: TRIB1 promotes GBM cell survival by upregulating survival signaling pathways like ERK and Akt, which leads to decreased effects of RT/TMZ therapy. Targeting TRIB1 would reduce oncogenic signaling in these cells and therefore may sensitize them towards RT/TMZ therapy.